Еволюція воєнно-політичної стратегії США в 40–70-ті роки ХХ ст. - Kolesnuk, Viktor; Podvernuk, Ludmyla; Колесник, Віктор; Подвернюк, Людмила (Східноєвропейський національний університет ім. Лесі Українки, 2013)
У статті проаналізовано й висвітлено воєнно-політичну стратегію США в 40–70-роки ХХ ст. Визнано, що основним складником глобальної стратегічної американської місії є засоби воєнно-політичної сили: стрімка зовнішньополітична активізація, експансія, поразки на периферії, наступне прагнення до консолідації зон впливу, що збереглися, й паралельно – хвиля волюнтаристського бажання домогтись ізоляції й воєнного оточення СРСР – головного суперника у післявоєнному світі.The article analyzes and highlights the military and political strategy in the U.S. 40¬70 years of the twentieth century. It is recognized that the main component of U.S. global strategic mission is a means of military and political power: the rapid intensification of foreign policy, expansion, lesions in the periphery, following the desire to consolidate zones of influence, preserved, and in parallel - a wave of forcible isolation and a desire to achieve military encirclement of the USSR - the main rival in the postwar world. Incrementally describes the military and political concepts such as the concept of «containment», «prevetattive war» «flexible response», «massive retaliation». Describes the creation of NATO and the highlights of his official duties.
The Evolution of the Military and Political Strategy in the U.S. 40–70 Years of the Twentieth Century
Keywords: США; експорт капіталу; воєнно-політична стратегія; дипломатія; «світовий порядок»; USA; export of capital; the military-political strategy; diplomacy; «world order»